Educational Permanence Project in a Residential Program for minors consuming psychoactive substances: A look from the Guidance discipline in Costa Rica - González Palacios, Zeanne (2025)
The Educational Permanence project is managed in the Casa JAGUAR Residential Program, which is an institution of the Costa Rican Country, which seeks to provide comprehensive care to minors consuming psychoactive substances. This article was based on the methodological strategy called Systematization of Experiences and according to Jara (2012) it is understood as “historical and complex processes in which different actors intervene and that are carried out in a specific economic, social, cultural context and in particular organizational or institutional situations” (p. 60). The central axis of this study was the analysis of the management process to implement the Educational Permanence Project in the Casa JAGUAR Residential Program between the years 2020 and 2022. The instruments for recording and organizing information were logs, work reports, emails and minute books. The main learnings from the project were the controversies and omissions generated by the absence of a due process scheduled and organized jointly with the corresponding interdisciplinary team. In contrast, among the strengths of the project, the constant coordination with inter-institutional networks (persons representing the Ministry of Public Education and the University of Costa Rica) stood out. These entities, together with Casa JAGUAR, favored the protection of the right to study during the process of internment.